Making Humans Matter In Art: A Southeast Asian Lens - Bridget Tracy Tan (IJCAS (International Journal of Creative and Arts Studies), 2025)
The age of mass media, AI, machine learning and LLMs (large language models) has considerably diminished concepts of an original visual language in painting and related visual arts. If we regard the visual language as conveying values across humanity, what then does this erosion speak of in civilisation? In representation, what are artists creating and what are audiences looking at inside the artwork? How can we elucidate human values, and understand the nexus of historical depth, the problematisation of geopolitical identities and aesthetics all at once in 'art'? Referencing examples of contemporary Southeast Asian artists in painting and image making, this presentation suggests a relationship of space in the visual field to consciousness - consciousness, as the wellspring of values. This hopefully facilitates new ontological refraction in an increasingly volatile, cultural environment. How can Southeast Asian art speak to its region? How can it rationalise the global environment at a breaking point? How can it generate empathy and care, that we might learn to become human again? Menjadikan Manusia Bermakna dalam Seni: Perspektif Asia TenggaraAbstrak Era media massa, kecerdasan buatan (AI), pembelajaran mesin, dan LLM (large language models) telah secara signifikan mengikis konsep bahasa visual yang orisinal dalam seni lukis dan seni visual terkait. Jika bahasa visual dipahami sebagai medium penyampai nilai-nilai kemanusiaan, maka apa makna pengikisan tersebut bagi peradaban? Dalam praktik representasi, apa yang sesungguhnya diciptakan oleh seniman dan apa yang dilihat oleh audiens di dalam karya seni? Bagaimana kita dapat mengelaborasi nilai-nilai kemanusiaan serta memahami keterkaitan antara kedalaman historis, problematisasi identitas geopolitik, dan estetika secara simultan dalam “seni”? Dengan merujuk pada contoh seniman Asia Tenggara kontemporer dalam seni lukis dan penciptaan citra, presentasi ini mengemukakan adanya relasi antara ruang dalam medan visual dan kesadaran—di mana kesadaran dipahami sebagai sumber utama nilai-nilai. Pendekatan ini diharapkan dapat memfasilitasi pembiasan ontologis baru dalam lingkungan kultural yang kian bergejolak. Bagaimana seni Asia Tenggara dapat berbicara kepada wilayahnya sendiri? Bagaimana ia dapat merasionalisasi lingkungan global yang berada di titik kritis? Bagaimana seni dapat menumbuhkan empati dan kepedulian, agar kita dapat belajar untuk menjadi manusia kembali?